2002
DOI: 10.1105/tpc.003939
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of CVP1 Reveals a Role for Sterols in Vascular Patterning

Abstract: Vascular cell axialization refers to the uniform alignment of vascular strands. In the Arabidopsis cotyledon vascular pattern1 ( cvp1 ) mutant, vascular cells are not arranged in parallel files and are misshapen, suggesting that CVP1 has a role in promoting vascular cell polarity and alignment. Characterization of an allelic series of cvp1 mutations revealed additional functions of CVP1 in organ expansion and elongation. We identified CVP1 and found that it encodes STEROL METHYLTRANSFERASE2 (SMT2), an enzyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(191 citation statements)
references
References 57 publications
14
176
0
1
Order By: Relevance
“…This alteration of sterol profile is consistent with the loss or reduction of SMT2 function and is similar to the situation described for co-suppressed 35S::SMT2 Arabidopsis plants (Schaeffer et al 2001), and cvp1 (Carland et al 2002) and frl1 (Hase et al 2005) mutants that have a mutation in SMT2. Similar alterations were observed in SMT3-RNAi lines (#1, #2, and #3), with increased levels of campesterol (1.8-fold), campestanol (1.9-fold), and brassicasterol (2.0-fold).…”
Section: Altered Sterol Profile In Smt-rnai Transformed Hairy Rootssupporting
confidence: 87%
See 1 more Smart Citation
“…This alteration of sterol profile is consistent with the loss or reduction of SMT2 function and is similar to the situation described for co-suppressed 35S::SMT2 Arabidopsis plants (Schaeffer et al 2001), and cvp1 (Carland et al 2002) and frl1 (Hase et al 2005) mutants that have a mutation in SMT2. Similar alterations were observed in SMT3-RNAi lines (#1, #2, and #3), with increased levels of campesterol (1.8-fold), campestanol (1.9-fold), and brassicasterol (2.0-fold).…”
Section: Altered Sterol Profile In Smt-rnai Transformed Hairy Rootssupporting
confidence: 87%
“…The Arabidopsis genome contains three distinct genes encoding sterol-C24-methyltransferases (SMTs) involved in sterol biosynthesis (Figure 4). SMT2 and the functionally redundant SMT3 mainly catalyze a second methyl transfer, as a branch point distinguishing the sterols from brassinosteroid precursors (Bouvier-Navé et al 1997;Carland et al 2002).…”
Section: Generating Arabidopsis Root Culture Lines With Reduced Exprementioning
confidence: 99%
“…However, lipid biosynthesis pathways have been elucidated in the regulation of endomembrane trafficking of PIN proteins. In Arabidopsis, sphingolipids and sterols have been shown to be involved in the regulation of PINs and AUX1 to maintain their polar subcellular localization (24,28,38,39). Sterols have been implicated in trafficking of PIN2 in its membrane domain.…”
Section: Significancementioning
confidence: 99%
“…In this mutant, PIN2 endocytosis and root gravitropism was compromised as the result of altered sterol composition (27). Another mutant, cotyledon vascular pattern 1(cvp1), which is a knock-out mutant of STEROL METHYLTRANSFERASE2 (SMT2), a key enzyme in the sterol biosynthetic pathway, displayed abnormal vascular cell polarity and defectiveness in cell elongation (39,40). The results from ceramide mutants indicate that sphingolipids with very long acyl chains define a trafficking pathway with specific endomembrane compartments and polar auxin transport proteins (25).…”
Section: Significancementioning
confidence: 99%
“…However, a recent study has shown that polarized localization of the AtPIN1 and AtPIN3 proteins requires STEROL METHYLTRANSFERASE1 (SMT1) function, possibly providing clues as to the origins of some of the developmental defects, especially regarding vascular development, which are observed in the smt1 (orc) mutant (Willemsen et al 2003). Interestingly the STEROL METHYLTRANSFERASE2 (SMT2/CVP1) gene has also been implicated in vascular patterning, suggesting that it may be involved in similar processes (Carland et al 2002).…”
Section: Perspectives: New Stitches In the Offingmentioning
confidence: 99%